2017
DOI: 10.17957/ijab/15.0348
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of 2-Cys Prx Increased Salt Tolerance of Photosystem II in Tobacco

Abstract: To explore the plant active oxygen scavenging and photosynthesis function of 2-Cys Prx, a newly discovered member of the antioxidant protease family, the tobacco 2-Cys Prx gene was cloned into the plant expression vector prok II. This vector, which is controlled by the constitutive strong promoter CaMV35S, was introduced into tobacco by Agrobacteria-mediated transformation. The 816-bp open reading frame of tobacco 2-Cys Prx encodes 271 amino acids and showed high homology with 2-Cys Prx genes from Solanum lyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The effects of different types of sodium salt stress on the PQ pool of the sorghum leaves were not significant, and the differences among different types of sodium salt treatments were small. The differences among different types of sodium salt stress were not significant for V I , there were some increases in the relative variable fluorescence V K at 0.3 ms point K. The increase in V K is considered to be a specific sign of damage to the oxygen-evolving complex (OEC) on the electron donor side of PSII (Zhang et al 2017). These results indicated that the OEC was affected by different types of sodium salt stress, but the sensitivities showed no significant differences under the stresses of alkaline salts from that of neutral salts.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of different types of sodium salt stress on the PQ pool of the sorghum leaves were not significant, and the differences among different types of sodium salt treatments were small. The differences among different types of sodium salt stress were not significant for V I , there were some increases in the relative variable fluorescence V K at 0.3 ms point K. The increase in V K is considered to be a specific sign of damage to the oxygen-evolving complex (OEC) on the electron donor side of PSII (Zhang et al 2017). These results indicated that the OEC was affected by different types of sodium salt stress, but the sensitivities showed no significant differences under the stresses of alkaline salts from that of neutral salts.…”
Section: Discussionmentioning
confidence: 98%
“…The increase of the relative variable fluorescence V k at the K point (300 μs) was due to the inhibition of the water-splitting system and the partial suppression of the acceptor side before Q A (Figure 3(D,E)). The K step of the chlorophyll a fluorescence transient (quantified as V K ) is an indicator of OEC injury in the photosynthetic apparatus (Strasser 1997;Zhang et al 2017). The K phase was clearly visible in the standardized O-J curve (Figure 3(D,E)), and V K also increased significantly under NaCl stress (Figure 3 (D,E)).…”
Section: Mt Inhibited Ros Production By Promoting Psii Repairmentioning
confidence: 99%
“…The K phase was clearly visible in the standardized O-J curve (Figure 3(D,E)), and V K also increased significantly under NaCl stress (Figure 3 (D,E)). The increase in V K is considered to be a sign of damage to the oxygen-evolving complex (OEC) on the electron donor side of PSII (Zhang et al 2017). However, the increase in V K was reduced when exogenous MT was applied (Figure 3(D,E)).…”
Section: Mt Inhibited Ros Production By Promoting Psii Repairmentioning
confidence: 99%
“…Under adverse conditions, plant photosynthetic electron transport is often blocked on the electron donor and acceptor sides of the PSII reaction center; the transfer of QA to QB is the main inhibitory site (Zhang et al 2019b). The increase in the relative variable fluorescence VJ at point J (2 ms) on the normalized O-P curve indicated that the electron transfer from QA to QB in the photosynthetic electron transport chain was blocked (Zhang et al 2017(Zhang et al , 2018c. The increase in the relative variable fluorescence VK at point K (0.3 ms) on the normalized O-J curve was considered a specific marker of the damage to the activity of oxygen-evolving complex on the PSII electron donor side (Zhang et al 2012(Zhang et al , 2016.…”
Section: Discussionmentioning
confidence: 99%